2021
DOI: 10.1371/journal.pone.0243782
|View full text |Cite
|
Sign up to set email alerts
|

Patient harm associated with serial phlebotomy and blood waste in the intensive care unit: A retrospective cohort study

Abstract: Background Intensive care unit (ICU) patients are at high risk of anemia, and phlebotomy is a potentially modifiable source of blood loss. Our objective was to quantify daily phlebotomy volume for ICU patients, including blood discarded as waste during vascular access, and evaluate the impact of phlebotomy volume on patient outcomes. Methods This was a retrospective observational cohort study between September 2014 and August 2015 at a tertiary care academic medical-surgical ICU. A prospective audit of phleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 37 publications
0
50
0
1
Order By: Relevance
“…The volume of blood typically needed for BGA is approximately 2 mL, for serum chemistries it is 7.5 mL, for citrate tubes it is 4.3 mL, for EDTA it is 2.7 mL, and it is up to 6 × 10-20 mL for blood cultures. A systematic review by Siegal et al pointed out that only 10% of collected 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The volume of blood typically needed for BGA is approximately 2 mL, for serum chemistries it is 7.5 mL, for citrate tubes it is 4.3 mL, for EDTA it is 2.7 mL, and it is up to 6 × 10-20 mL for blood cultures. A systematic review by Siegal et al pointed out that only 10% of collected 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some patients have an increased risk for iatrogenic anemia. Single multicenter studies identified the following risk groups suffering from anemia caused by blood loss: septic patients, patients with organ dysfunctions, transplanted patients, patients with renal failure (specifically renal replacement therapy), ventilated patients, patients receiving RBC transfusions, elderly persons, Jehovah's Witnesses, and neonates [2,11,49,56,71,72]. Especially in septic patients, a hemoglobin decrease of −0.82 ± 0.81 g/dL per day within the first 3 days and a decrease of −0.3 g/dL per day for every further day was observed [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations